The Impact of Digital Advertising on Online Consumer Behavior: Visual Trends and Future Research Directions - Syamsudin, Moch. Rizal; Rosdiana Noer, Lissa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In today’s digital era, digital advertising has reshaped how we shop and engage with brands. This study aims to analyze the development and research trends concerning the impact of digital advertising on online consumer behavior through a bibliometric analysis of Scopus indexed articles. The findings reveal that digital advertising has transformed brand consumer interactions through social media, e-commerce, and search engines, with an emphasis on building loyalty and trust through personalized strategies. Key findings indicate the dominance of topics such as social media marketing, consumer engagement, and online shopping behavior in the literature, with a significant upward trend. The study also identifies critical challenges, including data privacy concerns and the younger generation’s difficulty in distinguishing between content and advertising. Collaboration analysis reveals disparities in research participation, with Western countries still leading, while developing nations like Indonesia show promising potential. The study recommends further exploration of emerging technologies such as artificial intelligence (AI) and augmented reality (AR) in digital advertising, along with interdisciplinary approaches to understand the dynamics of consumer behavior in the digital age. The implications of this research contribute both to academic development and to more effective and ethical digital marketing practices.